Economic evaluation of the second-line regimen of liposome irinotecan (II) combined with 5-FU/LV versus placebo combined with 5-FU/LV for locally advanced or metastatic pancreatic ductal adenocarcinoma in China - Jinlong Huang; Hanyun Ye; Jingyang Lin; Dan Luo; Ping Huang; Xiaochun Zheng (PLoS ONE, 2026)
Background The cost-effectiveness of liposome irinotecan (II) (HR070803) in combination with 5-fluorouracil and leucovorin as a treatment for patients with locally advanced or metastatic pancreatic ductal adenocarcinoma offering a potential new standard of care has not been established. Considering the high cost of liposome irinotecan (II), the aim of this study was to evaluate the economic value of liposome irinotecan (II) combined with 5-fluorouracil and leucovorin（5-FU/LV） versus placebo combined with 5-FU/LV for this indication from the perspective of the Chinese healthcare system. Methods We developed a three-state Markov model based on the trial: NCT05074589 to estimate lifetime costs, quality-adjusted life-years (QALYs), and incremental cost-effect ratios (ICERs) in terms of cost per QALY gained. The utility of health status and the disutility of adverse events were obtained from the published literature. Costs were obtained from local hospitals and published literature. Costs and outcomes were discounted at a discount rate of 5% per year. To assess the robustness of the model, univariate and probabilistic sensitivity analysis was performed. Results In the base-case analysis, liposome irinotecan (II) regimen provided an additional 0.08 QALYs compared to the placebo regimen with an ICER of $310,418.81/ QALY gained, which indicates that the liposome irinotecan (II) regimen is not cost-effective at the $39,221.95/ QALY threshold. One-way sensitivity analyses showed that the model was most sensitive to the utility of PFS, the cost of liposome irinotecan (II), and the utility of PD. Probabilistic sensitivity analyses showed that the liposome irinotecan (II) regimen had a probability of 0 for having a cost effect at $39,221.95/ QALY. Price simulations show that the liposome irinotecan (II) option is cost-effective at a willingness-to-pay (WTP) of $39,221.95/QALY if the price of liposome irinotecan (II) is reduced to $2.93/mg (88.6% reduction). Conclusions From the perspective of the Chinese healthcare system, liposome irinotecan (II) in combination with 5-FU/LV was less cost-effective than placebo in combination with 5-FU/LV for locally advanced or metastatic pancreatic ductal adenocarcinoma.